Even energy consumption and backside routing: An improved routing protocol for effective data transmission in wireless body area networks - Ilkyu Ha (International Journal of Distributed Sensor Networks)
One of the core technologies of wireless body area networks (WBANs) is the routing technology. For effective routing in WBANs, various network operations such as lifetime extension and energy efficiency are required to be considered. However, the characteristics of the body serve as the most important management elements for stable operation and for guaranteeing effective WBAN management. Therefore, in this study, a routing protocol, even energy consumption and backside routing, is proposed and designed for stable operation of WBANs; it considers even energy consumption for the lifetime extension of the network and the path loss of the node located at the back of the body. For this study, the Mobile-ATTEMPT (M-ATTEMPT) as a recent routing technology is analysed, and an improved algorithm is proposed. Finally, the excellence of the proposed protocol is proved through a variety of experiments. The results show a significant improvement than previous routing technologies in terms of network lifetime, throughput and residual energy.